(untitled) (Journal of Science and Technology, 2016)
Several factors affect wood durability but the influence of anatomy is scarcely studied. Vessels and fibres sampled across and along stems of Milicia excelsa (Welw.) C. C. Berg) (odum), En- tandrophragma cylindricum (Sprague) Sprague (sapele), Terminalia ivorensis A. Chev. (emire) and Antiaris toxicaria Lesch. (kyenkyen) were studied to understand the relationship between their vessel-fibre (V-F) ratios, specific gravities (SGs) and durabilities. Vessels, fibres and their proportions were examined from macerates and T.S. of prepared slides. While the timbers ex- hibit major hardwood cell-types (e.g. vessels, fibres and parenchyma), intra-stem variability ex- ists with more vessels and greater V-F ratios at the crowns and in sapwoods than at the butts and in heartwoods, unlike for fibres. Inter-specific variation also shows A. toxicaria has the greatest vessel content then T. ivorensis, E. cylindricum and M. excelsa, a contrary pattern for fibre con- tents. V-F ratio ranks as: A. toxicaria > E. cylindricum > T. ivorensis > M. excelsa, while SGs are higher in E. cylindricum (667) and M. excelsa (635) than in T. ivorensis (507) and A. toxi- caria (505), which hardly differ from published data. Except for E. cylindricum, butts have the greatest SGs. Correlations between their V-F ratios and SGs are R2 = 34%, 84%, 32% and 1% respectively. Timbers with greatest vessels and V-F ratios but least fibres and SGs have weak relationship and very low durabilities, as in A. toxicaria (R2 = 1%). However, M. excelsa, which has the strongest V-F ratio and SG relationship (R2 = 84%), is very durable.